Peran Notaris dalam Pembuatan Akta Pernyataan Keputusan Rapat Umum Pemegang Saham (RUPS) Perseroan Terbatas di Kota Semarang - Fitri, Aulia Ineke; Mahmudah, Siti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
In its implementation, the General Meeting of Shareholders (GMS) is recorded in the form of meeting notes in the form of a notarial deed and/or backhand deed which is then recorded in the form of a deed. This research method uses a sociological legal approach. The purpose of this study was to determine the role of a notary in making the decision deed of the General Meeting of Shareholders (GMS) of a limited liability company in the city of Semarang. From the results of the examination, the notary is not involved in the decision- making process of the GMS. The task of a notary in making a deed of the decision of a meeting of shareholders of a company is very limited, such as in making a party deed, the notary is only limited to pouring it into a legalized deed.